Pendidikan Multikultural Dipesantren - sunarto, sunarto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Indonesia is a country made up of islands separated and bounded by the sea, so that Indonesia is a country that has a cultural diversity. The motto 'unity in diversity is a symbol which indicates that Indonesia is a unit that consists of diverse ethnicity,  religion, language and  culture  that  accompanies  it.  Indonesia's  diverse  cultures  of  the  value  of  pluralism  and multicultural, this must be addressed as a personality trait and pluralistic nation and a nation's wealth. Cultural differences should not be treated as a barrier and trigger conflict.Indonesian  society  should  contribute  to  achieve  this  goal  is  no  exception  younger generation,  mostly  students.  To  build  that  education  is  an  excellent  medium  to  educate  the nation's children are students as a potential successor to the nation to understand the cultural diversity  of  Indonesia  and  accept  cultural  differences  such  as  the  legacy  of  a  country  that always maintained its existence.Education  is  taught  must  be  in  accordance  with  the  approach  defined multiculturalism  as  an  expression  of  awareness  of  cultural  diversity,  human  rights,  and  the reduction or elimination of various types of prejudices to build a fair society and a life ahead. The education system in Indonesia is regulated and defined in an Act in the form of a national education system that is defined in the Act No. 20 of 2003.